Exploration of the Views of Eshop Managers on eWOM in the Czech Republic - Laboutka, Filip; Kottika, Efthymia, 1982-; Karlíček, Miroslav, 1979-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
This study focuses on views of e-shop managers on eWOM in Czech Republic. It aims to explore and investigate managers’ knowledge, behaviour, and opinions on online communication regarding their business and products. The research method that is used is explorative qualitative research using semi-structured interviews to collect data. Among findings of the research is that participating e-shop managers have a gist of eWOM, monitor independent platforms, know that responding to negative eWOM is beneficial to their brand, know which eWOM channel is the most important for their business, and respond to negative eWOM with caution. Apart of these findings, there are several observations related to negative reviews and established theory. These observations as well as findings of this research pave the way for more extensive qualitative research of this issue.
Vedoucí práce: Efthymia Kottika
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses